PENGARUH PEMBERDAYAAN KADER DALAM PENERAPAN KARTU PEMANTAUAN MANDIRI (KPM) TERHADAP PENCEGAHAN GANGGUAN PERGERAKAN AKIBAT ASAM URAT PADA LANSIA - Utami, Putu Ayu Sani; Sahar, Juniati; -, Widyatuti (Coping: Community of Publishing in Nursing; Vol 3 No 3 (2015): JURNAL EDISI SEPTEMBER-DESEMBER 2015, 2015)
Independent Monitoring Card (IMC) makes elderly become independent in managing health and controlling risk of gout. The IMC applied integration of functional consequences theory, management theory, community as partners, family centered nursing, Arthtritis Self Management Program and elderly KMS. The results showed that 9 cadres have increased ability to apply IMC in order to prevent interference with the movement as a result of uric acid problems in the elderly on the results of the Wilcoxon test with p value of 0.000 which gives the sense that there is the influence of empowerment cadres in the application card independent monitoring (KPM) on the prevention of movement disorders as a result of acid veins in elderly. Pain scale of the elderly with uric acid problems decreased from 6,02 to 4,50 and uric acid reduction levels in elderly men 1,93 mg/dl while women 2,02 mg/dl. The improved health of the elderly is also indicated by 10 families assisted. Department of Health, health centers, community nurses and community are advised to use IMC as a solution to solve movement disorders due to uric acid among elderly.
Keywords: elderly, Independent Monitoring Card (IMC), movement disorders, uric acid